KAJIANSOSIAL-EKONOMI UMKM "WIRELESS FIDELITY (WIFI)" DI PERUM MAESA UNIMA - Romi Mesra; Manuel E. Korompis; Paulus R Tuerah (Jurnal Riset Entrepreneurship, 2023)
The purpose of this research is to examine the socioeconomic wireless fidelity (wi-fi) company as one of Perum Maesa Unima's SMEs. The qualitative research technique utilized in this study, also known as scientific research, is research that does not include computations and emphasizes the natural character of data sources. The most significant and fundamental analysis in employing qualitative data, according to Miles and Huberman, is data reduction, presentation, and conclusion. Data collecting methods such as observation, interviews, and documenting. The findings of this study show that students require the internet, that SMEs profit from students as Wi-Fi users, and that students must adapt to the internet as part of the learning process in higher institutions.